Ductile failure prediction using phenomenological fracture model for steels: calibration, validation and application. - Cuenca Cabrera, Carlos Andres (2018)
The present thesis shows the analysis, calibration, and application of the stress modified criticai strain criterion to predict ductile failure for an A285 steel. To obtain the mechanical behavior of the material, experimental tests were carried out by implementation of 5 different types of geometries: smooth round bar, notched round bar (R=1 , 2, 3 mm), and, deep and shallow cracked SE(B) specimens. Then, for the calibration process of the mechanical properties finite element models were generated, using 30 solid elements with 8 nodes (C308), matching the geometry and the properties of the tested specimens. To calibrate the elastoplastic behavior was used the experimental and numerical response obtained from the smooth and notched round bar specimens; and, for the damage calibration was used the responses obtained from both deep and shallow crack SE(B) specimens. Once the mechanical properties were calibrated, then there were obtained the SMSC criterion factors represented by the equation ..... and, the damage condition which is represented by the displacement at failure (.......) and exponential factor (....). This calibrated model was able to recover the SE(B) experimental responses that validate the use of the characterized material in a complex structure. Then, the fully characterized material was applied in two pipelines which have externai initial circumferential elliptical crack; being the first one pipe with shallow crack and the second one with deep crack. Finally, both pipes were submitted to tension loads to predict the ductile damage behavior, obtaining the necessary load to the crack start growing, and the evolution of the failure.